Atropine and scopolamine in leaf and flower of Datura arborea L. - Miklós, E. J.; Botz, L.; Horváth, Gy.; Farkas, Á.; Dezső, Gy.; Szabó, L. Gy. (International Journal of Horticultural Science, 2001)
Angel's trumpet (Danira = Brugmansia arhorea) is a common, popular ornamental plant in Hungary. On the basis of thin layer chromatographic and densitometric alkaloid studies of leaf and flower samples collected from several places in Somogy and Baranya counties it can be stated that in samples of cultivars with different flower colour, taken approximately at the same time, the atropine and scopolamine content varies: there are samples free of alkaloids, but most of them are rich in alkaloids. Although the means do not reflect the extremes, they are suitable for determining the alkaloid accumulating capacity of flowers. Generally the amount of atropine and scopolamine is significant both in the leaf and the flower. It is conspicuous that the flower can be characterised by an extremely high scopolamine content (mean in mg/g dry matter of leaf: atropine 0.34, scopolamine 0.31; of flower: atropine 0.26, scopolamine 0.85). Thus it can be stated that the leaf, and especially the flower of angel's trumpet is a potential hallucinogen, just like in the case of Datura stramonium.